Developing cultural awareness in human service professionals: A personal journey - Sturgeon, S (Social Work/Maatskaplike Werk, 2002)
In order to function appropriately and sensitively in a rapidly changing multi-cultural/racial society such as South Africa, human service professionals must be aware of their own life experiences and how these have contributed to the development of their prejudices. This awareness also sensitises them to the development of prejudice, and therefore promotes a better understanding and tolerance of the prejudice of others, and the way that this prejudice can be altered. Students in the Department of Social Development are required to write an "Ethnic Autobiography", tracing their life history in terms of their awareness and experience of their own and other ethnic groups, how this awareness was developed and their current attitudes. This experience forms the experiential component of a module on anti-discriminatory practice and is described by students as a very powerful and sensitising experience.